1981
DOI: 10.1017/s002185960006617x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of delayed sowing and weather on growth, development and yield of winter oil-seed rape (Brassica napus)

Abstract: Sowing winter oil-seed rape cv. Victor late in autumn (late September or October) in seven seasons from 1970 to 1977 gave enormously variable seed yields, from 120 to 450 g/m 2 . All crops made little growth before winter, and yield was related to the size of the crop at flowering, a function of the length of time for radiation interception and growth between the 'beginning of spring', when mean temperatures rose consistently above 5 °C, and full flower in late May. A late spring in 1970 gave the poorest growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
1
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(126 citation statements)
references
References 14 publications
10
111
1
1
Order By: Relevance
“…Mendham et al (1981) also have reported similar results. These results were confirmed using an apetalous flower line (Rao et al, 1991).…”
Section: Effect Of Endogenous and Environmental Factors On No 3 ؊ Influxsupporting
confidence: 66%
See 1 more Smart Citation
“…Mendham et al (1981) also have reported similar results. These results were confirmed using an apetalous flower line (Rao et al, 1991).…”
Section: Effect Of Endogenous and Environmental Factors On No 3 ؊ Influxsupporting
confidence: 66%
“…The two constitutive and inducible components of each transport system (high or low affinity) were assumed to be similarly regulated by these compounds. The effect of PAR was taken into account in the model from bolting to harvest according to Chapman et al (1984) and Mendham et al (1981), who have demonstrated a decrease of about 60% to 80% of PAR transmitted inside the rape canopy at the beginning of flowering. No interaction between climatic factors (temperature and PAR) was taken into account.…”
Section: Total N and Isotopic Analysesmentioning
confidence: 99%
“…Several approaches from, for example, France and Germany take the amount of N in the WOSR canopy at the end of autumn growth and/or at the beginning of spring growth into account [18][19][20]. In one study of insignificant leaf losses over winter, a well-developed rapeseed canopy showed a higher leaf area index at the beginning of spring growth than a poor canopy, which, in consequence, allows for reduced N fertilization rates [21]. Henke et al [19] showed that even if canopy N is lost over winter due to frost, optimum N requirements in spring decreased with increasing canopy N in late autumn.…”
Section: Introductionmentioning
confidence: 99%
“…With the research that the researcher performed in the condition of humidity stress on Sulphur in Rapeseed (Brassica napus), they reached to this conclusion that the harsh reduction of sulphur in the Rapeseed (Brassica napus)'s organs would reduce the production of chlorophyll and photosynthesis reduction and the producing the dry substance would reduce and also the indicator of the harvesting would be reduce too [4] . Mendham et al [6] are believe that with the reduction of absorbing Sulphur in the condition of dry stress besides the function reduction the efficiency amount o water consumption would also decreasing (WUE) in the Rapeseed (Brassica napus) and it would decrease the amount of leaf level indicator and so it would cause the increasing of roots in comparison with the aerial organs. Sulphur with synthesizing the protein in Rapeseed (Brassica napus) would cause the increasing of the plants tolerance toward the dry situation [2,5] , but in the situation of harsh drought stress with the intense reduction in absorbing the sulphur the synthesis of protein would decrease and in first step with the hydrolyze of protein and changing it to the simple saccharin would try to stabilize the osmosis potential and its ingredient relatively water content [11] but with the continues of the stress condition the Rapeseed (Brassica napus) would loose its tolerance and with decreasing in the turgor pressure the output of the water consumption would cause the harsh reducing of functioning [7,8] .…”
Section: Introductionmentioning
confidence: 99%